Sanitasi Rumah Balita Penderita Pneumonia - Valensia, Rikza; Masra, Ferizal; Barus, Linda; Indarwati, Suami (MIDWIFERY JOURNAL, 2024)
Background: Pneumonia is an acute infection that attacks lung tissue (alveoli) caused by various microorganisms such as viruses, fungi and bacteria. The population susceptible to pneumonia are children aged less than 2 years, elderly aged more than 65 years and people who have health problems (malnutrition, immunological disorders). Risk factors for pneumonia are nutritional status, non-exclusive breastfeeding, vitamin A supplementation, zinc supplementation, low birth weight babies, vaccination, and indoor air pollution, especially cigarette smoke and burnt smoke from the kitchen.Objective: to determine the sanitary conditions of homes for toddlers with pneumonia in the working area of the Puskesmas Rajabasa Indah Bandar Lampung, such as ventilation, humidity, location of the kitchen, type of fuel used and air pollution in the home.Method: The research design used is descriptive research. The population and sample were 64 homes for toddlers with pneumonia in the working area of Puskesmas Rajabasa Indah Bandar Lampung. The research was carried out in April 2022Results: The results of the study showed that the houses of toddlers suffering from pneumonia in the working area of the Puskesmas Rajabasa Indah Bandar Lampung had ventilation that met the requirements of 68.7%, had humidity that met the requirements of 60.9%, the location of the kitchen met the requirements of 45.3%, which used kerosene for cooking is 84.3% and the remainder is still using firewood as much as 15.7%, and indoor air quality that meets the requirements is 84.3%.Conclusion: There are still many toddlers suffering from pneumonia who live in homes where sanitation conditions are still low. And the suggestion is that the Puskesmas Rajabasa Indah Bandar Lampung must provide education to the community about healthy homes so that the risk of disease arising from unhealthy home sanitation can be reduced. Keywords: Pneumonia, Home Sanitation, Toddlers  Latar Belakang: pneumonia adalah infeksi akut yang menyerang jaringan paru-paru (alveoli) yang disebabkan oleh berbagai mikroorganisme seperti virus, jamur dan bakteri. Populasi rentan terserang pneumonia adalah anak-anak usia kurang dari 2 tahun, usia lanjut lebih dari 65 tahun dan orang yang memiliki masalah kesehatan (malnutrisi, gangguan imunologi). Faktor risiko pneumonia adalah status gizi, ASI non eksklusif, suplementasi vitamin A, suplementasi zinc, bayi berat badan lahir rendah, vaksinasi, dan polusi udara dalam rumah terutama asap rokok dan asap bakaran dari dapur.Tujuan: Untuk mengetahui kondisi sanitasi rumah balita pneumonia di wilayah kerja Puskesmas Rajabasa Indah Bandar Lampung seperti ventilasi, kelembaban, letak dapur, jenis bahan bakar di dapur, dan polusi udara dalam rumah.Metode: Penelitian menggunakan rancangan deskriptif. Populasi dan sampel adalah 64 rumah balita pneumonia di wilayah kerja Puskesmas Rajabasa Indah Bandar Lampung. Penelitian dilaksanakan pada bulan April 2022Hasil: Hasil penelitian menunjukan bahwa rumah balita pneumonia di wilayah kerja Puskesmas Rajabasa Indah Bandar Lampung memiliki ventilasi memenuhi syarat sebanyak 68,7%, memiliki kelembapan memenuhi syarat 60,9%, letak dapur yang memenuhi syarat 45,3%, yang menggunakan minyak tanah untuk memasak sebesar 84,3% dan sisanya masih menggunakan kayu baakar sebanyak 15,7%, dan kualitas udara dalam rumah yang memenuhi syarat sebesar 84,3%.Kesimpulan: masih banyak balita pneumonia menempati rumah yang memiliki kondisi santiasi yang masih rendah. Dan sarannya adalah Puskesmas Rajabasa Indah harus melakukan penyuluhan ke masyarakat tentang rumah sehat agar dapat dikurangi resiko timbulnya penyakit yang disebabkan oleh kondisi sanitasi rumah yang tidak sehat. Kata Kunci: Pneumonia, Sanitasi Rumah, Balita